Alaska Building construction, Alaska-Yukon-Pacific Exposition, Seattle, Washington, 1909 - Curtis, Asahel, 1874-1941 (1909)
On verso of photograph: Alaska Bldg. Caption on image: x772 PH Coll 727.194 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number